Concurrent validity of individual differences in intelligence in activity differences of handicapped wheelchair users - Jipp, Meike; Wittmann, Werner W.; Badreddin, Essameddin (Proceedings of the Human Factors and Ergonomics Society 52nd annual meeting, 2008)
The following paper investigates the concurrent validity of individual differences at the lower end of the continuum of intelligence and especially with regard to the cognitive processes determining situation adaptation. These cognitive processes can be used for intention estimation behaviors for intuitive wheelchair control. After a theoretical overview discussing the potential relationship between situation adaptation and intelligence, a study was conducted with 16 wheelchair users whose intelligence scores deviated from the mean with about two standard deviations. Still, the individual differences at hand were highly predictive especially with regard to the durations of their operations and with regard to shifts of the order of operations. Implications of these results especially with regard to intention estimation behaviors and adaptive automation are discussed.